KARYA ROH KUDUS DALAM MENEMPATKAN PELAYAN GEREJA BERDASARKAN KIS 6:1-7 - Suhadi Suhadi; Iman Kristina Halawa (Manna Rafflesia, 2023)
This article aims to understand the work of the Holy Spirit in placing church ministers. The Holy Spirit reveals His work in placing church servants to develop ministry. However, based on this research, the author found several things that are of concern to a church minister. In Ex. 18:14-27 Jethro also asked Moses to appoint several people who could help him in leading God's chosen people. Likewise, what was experienced by the apostles in their ministry after they received the power of the Holy Spirit to preach the Gospel and convert many souls was recorded in Acts 2:41 as approximately three thousand souls; this figure is not a small number of souls who want to be served the truth. The work of the Holy Spirit enables church ministers to serve the congregation in terms of teaching God's Word. All of this happened inseparable from the work of the Holy Spirit, and the Holy Spirit also enabled the apostles to determine according to predetermined criteria; namely, people must be filled with the Holy Spirit, wise, and willing to suffer for the truth. Hopefully, this article can help to understand and understand the work of the Holy Spirit in the lives of believers in carrying out the church's tri-tasks in terms of ministry.